2006
DOI: 10.1051/0004-6361:20065392
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-FLAMES survey of massive stars: stellar parameters and rotational velocities in NGC 3293, NGC 4755 and NGC 6611

Abstract: An analysis is presented of VLT-FLAMES spectroscopy for three Galactic clusters, NGC 3293, NGC 4755 and NGC 6611. Non-LTE model atmosphere calculations have been used to estimate effective temperatures (from either the helium spectrum or the silicon ionization equilibrium) and gravities (from the hydrogen spectrum). Projected rotational velocities have been deduced from the helium spectrum (for fast and moderate rotators) or the metal line spectrum (for slow rotators). The origin of the low gravity estimates f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
138
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(161 citation statements)
references
References 62 publications
19
138
2
2
Order By: Relevance
“…The spectral types derived from the BCD method and those obtained by Evans et al (2005) using the MK system agree excellently. However, T eff values obtained with the BCD method show in general a good agreement with the values derived by Dufton et al (2006), although some discrepancies of about of 2000 K are observed in subtypes B1 and B2; i.e. NGC 4755 223 and NGC 4755 454 (see Table 15).…”
Section: Ngc 4755supporting
confidence: 71%
See 1 more Smart Citation
“…The spectral types derived from the BCD method and those obtained by Evans et al (2005) using the MK system agree excellently. However, T eff values obtained with the BCD method show in general a good agreement with the values derived by Dufton et al (2006), although some discrepancies of about of 2000 K are observed in subtypes B1 and B2; i.e. NGC 4755 223 and NGC 4755 454 (see Table 15).…”
Section: Ngc 4755supporting
confidence: 71%
“…(4) Spectral types taken from Schild (1970). (5) Spectral types taken from Evans et al (2005) and Dufton et al (2006).…”
Section: Fundamental Parameters Of the Starsmentioning
confidence: 99%
“…Nevertheless, depending on the statistical problem, the suited simplified functional form Π(x) is probably different. Moreover, this leads us to conclude that it is not enough to claim that Gaussian or Maxwellian distributions are consistent with the observed distributions simply because the first two moments (average and dispersion) coincide, as the literature sometimes concludes (e.g., Mokiem et al 2006;Dufton et al 2006b;Hunter et al 2008).…”
Section: F2 Triangular Functionsmentioning
confidence: 85%
“…Quantitative analysis of these objects was presented in a series of articles by Dufton et al (2006), Trundle et al (2007), Hunter et al (2007Hunter et al ( , 2008aHunter et al ( ,b, 2009a, and Dunstall et al (2011).…”
Section: Introductionmentioning
confidence: 99%